Think like a terrorist to combat terrorism and radicalization in prison - Sturgeon, William; Spina, Francesca (Boca Raton : CRC Press, 2022)
"Think Like a Terrorist to Combat Terrorism and Radicalization in Prison provides guidelines for hardening facilities, training staff, preparing for radicalized-terrorist inmates' incarceration, and monitoring these inmates after their release. The book combines practitioner experience with scholarly insights to offer practical suggestions bolstered by research. The authors offer suggestions for housing, programming, security, and staff training with the ultimate goal of keeping correctional facilities, staff, and other inmates, safe from radicalization and spreading terrorist doctrines and terrorist acts. This necessarily requires examining and potentially changing prison and guard policies and procedures, hiring and training suitable staff, and ensuring technology is available. Correctional facilities can curtail the recruitment and radicalization of inmates by developing staff training, de-radicalization programs, management methods, techniques, and practices that address the recruitment issues associated with this threat. The need for understanding, and the role line correctional officers and first-line supervisors play in preventing radicalization, is critical in this process. It is also vital to connect with, and maintain, communication with appropriate security and intelligence agencies as needed. Key Features: Outlines common terrorist and extremist activities in prison using relevant real-world examples Instructs on how to detect and recognize such efforts as recruitment and radicalization and how to curtail and prevent such activity Provides guidance on establishing de-radicalization programs within prison facilities Presents recommendations on collecting, analyzing, and disseminating intelligence to correctional, law-enforcement, and intelligence agencies on potential terrorist activities and recruitment efforts Think Like a Terrorist to Combat Terrorism and Radicalization in Prison provides the necessary instruction and situational awareness to help professionals recognize and curtail terrorist activities in prisons. Likewise, prison administrators and operators will gain a greater understanding of the challenges-and need for physical and operation security and establish policies and protocols-to identify and curtail radicalization within their facilities"--
Who Are Extremist-Terrorist Inmates and Other Extremist-Group Members, and Why Should You Care? -- What is Terrorism and What is its Scope? -- What are the Characteristics of Radicals and Potential Radicals -- Foreign and Domestic Terrorist-Extremist-Inmates versus Criminal Inmates -- Preparing, Planning, and Implementing Change -- People in the Matrix -- Places and Technology in the Matrix -- Staff Recruitment and Training -- Classification, Monitoring, Intelligence, Visiting, and Materials Review -- Inmate Programs and Programs Limiting Radicalization -- Islam, Religious Conversion and Imans -- Radicalization Recruitment within Correctional Facilities -- Inmate Vulnerability -- The Future Challenges of Extremist-Terrorist Inmates and Other Extremist Organizations in Correctional Institutions and Beyond -- Inmate Release and Probation and Parole -- The Next Steps.
OCLC-licensed vendor bibliographic record.
Keywords: Terrorism -- Prevention; Prisoners; Radicalization; Terrorists -- Recruiting; Corrections; COMPUTERS / Security / General; LAW / Forensic Science; POLITICAL SCIENCE / Political Freedom & Security / Terrorism